Application of iron ion cross-linked II type collagen gel in preparation of medicine for treating osteoarthritis
By hybrid ionic cross -linked gel prepared by hybrid ionic reactions with II collagen and iron ions, the problem of poor mechanical properties and degradation of collagen hydrogel when treating osteoarthritis is to promote the proliferation and adhesion of cartilage cells Attachment, anti -inflammatory and cartilage tissue regeneration effects.
Patent Information
- Application Number
- CN202310933999.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-01-28
AI Technical Summary
The existing collagen hydrogels have poor mechanical properties and are prone to degradation in the treatment of osteoarthritis, and cannot effectively restore the function of joint cartilage.
By hybridizing the II collagen solution with iron ion solution, the II collagen gel that is prepared by the iron ionic cross -linking of the iron ionic cross -linking has good biocompatibility and biological activity. Essence
The II -type collagen gel with iron ionic cross -linking significantly promotes the proliferation and adhesion of cartilage cells, has anti -inflammatory effects, can effectively regulate the expression of inflammatory factor -related genes, and promote the deposition of cartilage tissue regeneration and collagen fiber.
Smart Images

Figure CN119367264A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to the application of an iron ion cross-linked type II collagen gel in the preparation of a drug for treating osteoarthritis. Background Art
[0002] Osteoarthritis is a prevalent degenerative joint disease, often accompanied by chronic inflammation and articular cartilage defects, which seriously affects people's physical health and quality of life. According to statistics, there are more than 300 million OA patients worldwide. Since the self-healing ability of articular cartilage is extremely limited, timely surgical intervention is required, otherwise it will lead to disability of patients. Clinically, osteoarthritis is mainly treated by microfracture technology and tissue transplantation. However, these methods can only achieve structural filling of the defect site, and cannot achieve the restoration of articular cartilage function.
[0003] Collagen hydrogel has attracted much attention in the treatment of osteoarthritis because of its properties similar to those of natural cartilage tissue. Type II collagen is the main component of natural articular cartilage, with low immunogenicity, degradability, good biocompatibility and bioactivity. Type II collagen hydrogel can mimic the structure and function of the extracellular matrix of natural cartilage and can provide a suitable microenvironment for cell growth, proliferation and differentiation. However, collagen hydrogel has poor mechanical properties and is easily degraded, which limits its application in the clinical treatment of osteoarthritis.
[0004] Collagen cross-linking is a common method to improve its stability, which mainly includes chemical cross-linking and physical cross-linking. Chemical cross-linking can significantly improve mechanical properties and resist degradation by adding cross-linking agents such as glutaraldehyde, EDC / NHS and genipin, but the residue of chemical cross-linking agents may have toxic side effects. Physical cross-linking such as thermal dehydrogenation and ultraviolet radiation can also improve its stability, but these methods may cause collagen denaturation, thereby causing it to lose its biological activity.
[0005] Iron is an essential trace element for the human body and plays a key role in many important physiological processes of the human body. The inventor unexpectedly discovered that the gel prepared by mixing type II collagen solution with iron ion solution can treat osteoarthritis. The gel has good biocompatibility and biological activity, and can significantly promote cell proliferation, adhesion and cartilage differentiation; the hydrogel has an anti-inflammatory effect and can effectively regulate the expression of genes related to inflammatory factors; the hydrogel can repair articular cartilage defects in rats and promote collagen deposition and proteoglycan secretion. Summary of the invention
[0006] In view of the above technical problems, the purpose of the present invention is to provide an application of iron ion cross-linked type II collagen gel in the preparation of a drug for treating osteoarthritis. Specifically, the present invention includes the following contents:
[0007] The invention provides an application of an iron ion cross-linked type II collagen gel in preparing a medicine for treating osteoarthritis.
[0008] Preferably, the iron ion is Fe 3+ or Fe 2+ .
[0009] Preferably, the iron ion is Fe 3+ .
[0010] Preferably, the type II collagen is animal type II collagen.
[0011] Preferably, the type II collagen is yak type II collagen.
[0012] Preferably, the preparation method of the iron ion cross-linked type II collagen gel is: 3+ or Fe 2+ The solutions are mixed and reacted to obtain type II collagen gel cross-linked by iron ions.
[0013] Preferably, the pH of the type II collagen solution is 4.5-7.0.
[0014] The beneficial effects of the present invention are: ① The present invention finds that the iron ion cross-linked type II collagen gel not only has good biocompatibility and bioactivity, but also can promote the proliferation and adhesion of chondrocytes, and the cartilage differentiation of bone marrow mesenchymal stem cells; ② The present invention finds that the iron ion cross-linked type II collagen gel has a significant anti-inflammatory effect, can up-regulate anti-inflammatory factors and down-regulate the expression of genes related to pro-inflammatory factors; ③ The present invention finds that the iron ion cross-linked type II collagen gel can promote the regeneration of cartilage tissue, accelerate the deposition of collagen fibers and the secretion of proteoglycans; ④ The present invention finds that the iron ion cross-linked type II collagen gel can be used in the treatment of osteoarthritis in clinic. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Col II-Fe 2+ and Col II-Fe 3+In vitro biocompatibility and bioactivity of hydrogels; AC are live / dead cell staining (scale bar = 300 μm), live cell count, and CCK-8 assay results of chondrocytes after 1 day, 4 days, and 7 days of culture in hydrogels, respectively; D is phalloidin / Hoechst 33258 staining of chondrocytes after 4 days of culture in hydrogels (scale bar = 150 μm); EF are DNA and GAG content determination of chondrocytes after 1 day, 4 days, and 7 days of culture in hydrogels, respectively; GI are the relative expression levels of cartilage-specific genes Acan, Col2a1, and Sox9 of bone marrow mesenchymal stem cells after 4 days and 7 days of culture in hydrogels, respectively;
[0016] Figure 2 Col II-Fe 2+ and Col II-Fe 3+ Anti-inflammatory effect of hydrogels; A is the live / dead cell staining of RAW264.7 cells cultured in hydrogels for 4 days after H2O2 treatment (scale bar = 300 μm); BE are the relative expression levels of anti-inflammatory cytokine IL-10 and pro-inflammatory cytokines IL-18, IL-1β and TNF-α of RAW264.7 cells cultured in hydrogels for 4 and 7 days, respectively;
[0017] Figure 3 Col II-Fe 2+ and Col II-Fe 3+ Hydrogel promotes cartilage regeneration in vivo; A is the modeling and treatment of cartilage defects in SD rats; BD are the appearance images, ICRS appearance scores and Micro CT evaluation results of the articular cartilage defect site after 4, 8 and 12 weeks of gel implantation, respectively;
[0018] Figure 4 Histological evaluation of cartilage regeneration; AD are the results of H&E, Masson, Saf-O / FG staining and ICRS histological scoring (scale = 200 μm) of cartilage tissue regeneration 4 weeks, 8 weeks and 12 weeks after gel implantation, respectively. DETAILED DESCRIPTION
[0019] Example 1Col II-Fe 2+ and Col II-Fe 3+ Preparation of gel
[0020] Take a certain amount of ferrous sulfate (prepared and used immediately) and ferric chloride to prepare ferrous sulfate and ferric chloride aqueous solutions of a certain concentration. Add 13 mg / ml ferrous sulfate and 0.3 mg / ml ferric chloride aqueous solutions to a 5 mg / ml type II collagen solution with a pH of 7.0 to prepare yak collagen-Fe 3+ Mixed solution and yak collagen-Fe2+ The mixed solution was allowed to stand at room temperature for 0.5-12 h to form a gel.
[0021] Example 2 Cell culture
[0022] Rat articular chondrocytes (CP-R092) were cultured in DMEM F12 (Procell, PM150312, China) medium containing 15% fetal bovine serum (FBS, Gibco, Thermo Fisher Scientific, USA) and 1% anti-antibiotic (Antimycotic, Hyclone, USA); bone marrow mesenchymal stem cells (BMSCs, SCSP-402) were cultured in α-MEM (Gibco, Thermo Fisher, USA) medium containing 15% fetal bovine serum (FBS, Gibco, Thermo Fisher Scientific, USA) and 1% anti-antibiotic (Antimycotic, Hyclone, USA); RAW264.7 cells were cultured in α-MEM (Gibco, Thermo Fisher, USA) medium containing 10% fetal bovine serum (FBS, Gibco, Thermo Fisher Scientific, USA); The cells were cultured in DMEM medium (Procell, PM150210, China) supplemented with 1% penicillin-streptomycin antibiotics (Antibiotic-Antiycotic, Hyclone, USA). The culture conditions of the three cells were all 37°C and 5% CO2.
[0023] Example 3Col II-Fe 2+ and Col II-Fe 3+ Live / dead cell staining of gels
[0024] The hydrogel samples (Col II, Col II-Fe 2+ and Col II-Fe 3+ ) were mixed with chondrocytes to form a density of 2×10 5 cells / mL suspension. Then it was added to the laser confocal microplate and incubated for 1 day, 4 days and 7 days. At each time point, calcein-AM and propidium iodide (PI) were used to stain live and dead cells at 37°C for 1 hour. Finally, the cell fluorescence images were obtained by laser confocal microscopy, and the cells were counted using ImageJ.
[0025] The results are as follows Figure 1 As shown in A and B, A is Blank, Col II, Col II-Fe 2+ and Col II-Fe3+ Live / dead cell fluorescence staining at 1 day, 4 days and 7 days, B is the Image J cell counting result of A. The results show that chondrocytes in Blank, Col II, Col II-Fe 2+ and Col II-Fe 3+ All groups had good cell survival; with the increase of time, the number of cells in each group gradually increased, and the number of cells in Blank < Col II < Col II-Fe 2+ ﹤Col II-Fe 3+ Group.
[0026] Example 4Col II-Fe 2+ and Col II-Fe 3+ CCK-8 assay of gel
[0027] Add 100 μL of chondrocyte suspension (density 2×10 5 cells / mL) and incubated in a cell culture incubator for 24 hours. Then, Col II and Col II-Fe 2+ and Col II-Fe 3+ The hydrogel samples were added to a 96-well plate and incubated at 37°C for 1, 4, and 7 days. At each time point, 10 μL of CCK-8 was added and the absorbance at 450 nm was measured after incubation at 37°C for 30 minutes.
[0028] The results are as follows Figure 1 As shown in C. As the culture time increases, the number of cells gradually increases. On the 7th day, the number of cells is Blank﹤Col II﹤Col II-Fe 2+ ﹤Col II-Fe 3+ Therefore, iron ion cross-linked type II collagen can promote chondrocyte proliferation.
[0029] Example 3Col II-Fe 2+ and Col II-Fe 3+ Immunofluorescence staining of gel
[0030] Chondrocytes were mixed with hydrogel to form a suspension (2×10 5cells / mL) and added to a laser confocal microplate. After incubation at 37°C for 3 days, the cells were first fixed with 4% formaldehyde for 15 minutes and permeabilized with 0.1% Triton X-100 for 5 minutes; then blocked with 1% BSA in PBS buffer (10mM, pH 7.2-7.4) for 30 minutes at room temperature; finally, 100nM rhodamine-labeled phalloidin was used to stain the cell actin skeleton for 1 hour, and 5μg / mL Hoechst 33258 was added to stain the cell nucleus for 5 minutes. After staining, fluorescence images were captured using a laser confocal microscope.
[0031] The results are as follows Figure 1 As shown in D, Blank, Col II, and Col II-Fe 2+ and Col II-Fe 3+ The results showed that in Col, Col II-Fe 2+ and Col II-Fe 3+ Chondrocytes adhered to the hydrogel had a delicate actin cytoskeleton structure, while the cytoskeleton structure of the Blank group was less developed and the number of cells was relatively small. 2+ and Col II-Fe 3+ The hydrogel provided a bioactive scaffold for cells and effectively promoted the adhesion and spreading of chondrocytes.
[0032] Example 4Col II-Fe 2+ and Col II-Fe 3+ Determination of DNA and GAG content of gels
[0033] Chondrocytes were mixed with hydrogel to form a suspension (2×10 5 cells / mL), added to a 6-well plate and incubated in a cell culture incubator for 1 day, 4 days and 7 days. At each time point, after washing with PBS three times, proteinase K solution (20 mg / ml) was added for digestion at 60°C for 16 hours. After staining with Hoechst 33258 dye for 1 hour, the fluorescence intensity at 460 nm was measured by a fluorescence spectrometer to determine the relative content of DNA. At the same time, after staining with 1,9-dimethylmethylene blue (DMMB) for 30 minutes, the absorbance value at 525 nm was measured to determine the relative content of GAG. The DNA and GAG contents were normalized according to the Blank value on the first day.
[0034] The results are as follows Figure 1 As shown in E and F, E and F are Blank, Col II, Col II-Fe, respectively. 2+ and Col II-Fe3+ The DNA and GAG contents of the groups at 1 day, 4 days and 7 days. The experimental results showed that the DNA and GAG contents increased gradually with the increase of time, and Blank < Col II < Col II-Fe 2+ ﹤Col II-Fe 3+ Group.
[0035] Example 5Col II-Fe 2+ and Col II-Fe 3+ Expression of cartilage-specific genes in gel
[0036] Bone marrow mesenchymal stem cells and Col II, Col II-Fe 2+ and Col II-Fe 3+ The density of the gel mixture was 2×10 5 cells / mL suspension and incubated in 6-well plates for 4 and 7 days, respectively. Total RNA was extracted from cells using an RNA isolation kit. The concentration and purity of RNA samples were determined using a NanoDrop spectrophotometer. cDNA was synthesized using a PrimeScript RTreagent Kit and gDNAEraser, and gene expression levels were analyzed using TB Green Premix Ex Taq II. The expression of cartilage-specific genes was detected using a Real-Time PCR System. 2 -ΔΔCT The relative expression of the target gene was calculated by the method and normalized to the expression level of β-actin.
[0037] The results are as follows Figure 1 As shown in GI, G is the relative expression of Sox9 gene, H is the relative expression of Col2a1 gene, and I is the relative expression of Acan gene. After 7 days of cell culture, Sox9 was expressed in Col II, Col II-Fe 2+ and Col II-Fe 3+ The expression levels of Col2a1 increased by 1.7, 6.8, and 10.7 times in the three groups, respectively, while the expression levels of Acan increased by 2.9, 10.6, and 15.6 times, respectively. These results indicate that all hydrogels significantly upregulated these cartilage-specific genes. 2+ and Col II-Fe 3+ The three cartilage-specific genes in the group showed higher expression levels. 2+ and ColII-Fe 3+The hydrogel has excellent biological activity and significantly promotes the chondrogenic differentiation of bone marrow mesenchymal stem cells.
[0038] Example 6Col II-Fe 2+ and Col II-Fe 3+ Anti-inflammatory effects of the gel
[0039] The density is 2×10 5 RAW 264.7 cells / mL were placed in a laser confocal microplate containing 0.4mmol / L H2O2 solution and cultured for 1 day. Then the culture medium was removed and the hydrogel samples (Col II, Col II-Fe 2+ and Col II-Fe 3 + ) were added to the laser confocal microplate and co-cultured with cells for 4 days. Calcein-AM and propidium iodide (PI) were used to stain live and dead cells at 37°C for 30 minutes. Finally, cell fluorescence images were obtained by laser confocal microscopy. At the same time, RAW264.7 cells induced by H2O2 were co-cultured with Col II, Col II-Fe 2+ and Col II-Fe 3+ The hydrogel samples were co-cultured for 4 and 7 days, respectively. Total RNA was extracted from the cells using an RNA isolation kit. The concentration and purity of the RNA samples were determined using a NanoDrop spectrophotometer. cDNA was synthesized using a PrimeScript RT reagent Kit and gDNA Eraser, and gene expression levels were analyzed using TB Green Premix Ex Taq II. The expression of inflammation-related genes was detected using a Real-Time PCR System. -ΔΔCT The relative expression of the target gene was calculated by the method and normalized to the expression level of β-actin.
[0040] The results are as follows Figure 2 As shown, A is the live / dead cell staining of RAW264.7 cells, B is the expression of the anti-inflammatory factor IL-10 gene, and CE are the expression of the pro-inflammatory factors IL-18, IL-1β and TNF-α genes. The live / dead cell staining results showed that Col II-Fe 2+ Group and Col II-Fe 3+ The number of live cells in the Col II and Blank groups was significantly higher than that in the Col II and Blank groups, and no obvious dead cells were observed, indicating that Col II-Fe 2+ and Col II-Fe 3+ The hydrogel can effectively relieve inflammation. qRT-PCR results showed that Col II-Fe 2+and Col II-Fe 3+ The hydrogel upregulated the expression of the anti-inflammatory factor IL-10 gene and downregulated the expression of the pro-inflammatory factors IL-18, IL-1β and TNF-α genes. Therefore, iron ions endow type II collagen hydrogel with anti-inflammatory effects.
[0041] Example 7Col II-Fe 2+ and Col II-Fe 3+ Gel for cartilage regeneration
[0042] SD rats (male, 250-300 g) were housed in a standard laboratory. Before surgery, the rats were anesthetized by intraperitoneal injection of 10% (w / v) sodium pentobarbital (0.3 mL / 100 g). After shaving and disinfecting the surgical site, the skin and muscle tissue covering the left knee of each rat were cut with a scalpel to expose the joint pulley site. An electric drill was used to form a cylindrical cartilage defect with a diameter of 2 mm and a height of 2 mm at the pulley site of the left knee of each rat. 36 rats were randomly divided into a blank group, a Col II group, a ColII-Fe group, and a control group. 2+ Group and Col II-Fe 3+ In addition to the blank group, the hydrogel was injected into the surgical site to completely fill the defect. At different time points (4 weeks, 8 weeks and 12 weeks), 3 rats in each group were injected with an overdose of sodium pentobarbital and then sacrificed for specimen collection.
[0043] The experimental results are as follows Figure 3 As shown in B and C, B is the macroscopic image of the joint surface, and C is the ICRS macroscopic score. 2+ Group and Col II-Fe 3+ The tissue defects in the group were completely filled, while those in the blank group and the Col II group were only partially filled with fibrocartilage, and there were still obvious cracks in the blank group. After 8 weeks, all four groups showed relatively complete and uniform tissue regeneration. After 12 weeks, the Col II-Fe 2+ Group and Col II-Fe 3+ The surface of the regenerated cartilage in the Col II group was smooth and well integrated with the adjacent host cartilage; the new cartilage generated in the Col II group effectively occupied the defect site of the articular cartilage, but there was a significant difference from the natural tissue. Compared with the Col II group, the blank group showed a poorer quality of cartilage tissue. ICRS macroscopic scores showed that at 12 weeks, the Col II-Fe 2+ Group and Col II-Fe 3+ The ICRS value of the group was higher than that of the Col II group and the blank group, which was consistent with the results of macroscopic morphological observation.
[0044] After the collected specimens were immersed in 4% formaldehyde for 48 hours, the cartilage structure was carefully examined using a Micro-CT imaging device. The scanning voltage was 40 kV, the current was 250 μA, the exposure time was 240 ms, and the slice thickness was 0.1 mm. The results are shown in Figure 3 D. Twelve weeks after surgery, the surgical area of the blank group still had obvious defects, indicating that the self-repair ability of the subchondral bone is limited. The Col II treatment group showed a small amount of subchondral bone tissue at the defect site, indicating that the Col II hydrogel has the ability to promote subchondral bone regeneration. However, the Col II-Fe 2+ and Col II-Fe 3+ The group showed a large amount of new subchondral bone tissue and completely repaired the tissue defects, indicating that Col II-Fe 2+ and Col II-Fe 3+ Hydrogels can significantly promote subchondral bone regeneration.
[0045] Example 8Col II-Fe 2+ and Col II-Fe 3+ Histological staining of gel-regenerated cartilage
[0046] The fixed samples were immersed in 10% EDTA solution for 7 days to eliminate any calcified tissue. The samples were dehydrated in an alcohol gradient, then embedded in paraffin and sliced into 5 μm slices. The sections were stained with hematoxylin & eosin (H&E), Masson's trichrome staining (Masson), and Safranine O-fast green staining (Saf-O / FG) to detect the repair of cartilage defects.
[0047] The results of H&E staining are as follows Figure 4 As shown in A. After 4 weeks, Col II-Fe 2+ Group and Col II-Fe 3+ The defects in the control group were almost completely filled with new tissue; the blank group showed a large amount of tissue loss accompanied by severe inflammation. 2+ Group and Col II-Fe 3+ Sparse new chondrocytes appeared in the regenerated cartilage tissue of the group. 2+ and Col II-Fe 3+ The hydrogel group showed a large amount of dense and well-integrated new cartilage tissue, which contained abundant mature chondrocytes; the defects in the Col II group were filled with immature cartilage tissue; and a large amount of fibrocartilage was formed in the blank group. 2+ and Col II-Fe 3+ Hydrogel can effectively promote the regeneration of cartilage tissue.
[0048] Masson staining results Figure 4 As shown in B. 4 weeks after implantation, Col II-Fe 2+ and Col II-Fe 3+ A small amount of collagen fibers were observed in the cartilage defect of the hydrogel group. As time went on, the collagen fiber content in each group gradually increased. 2+ Group and Col II-Fe 3+ Masson staining results showed that Col II-Fe 2+ and Col II-Fe 3+ The hydrogel significantly accelerated collagen deposition.
[0049] Saf-O / FG staining results are as follows Figure 4 As shown in C. Four weeks after surgery, almost no obvious proteoglycan formation was observed in each group. Eight weeks after surgery, Col II-Fe 3+ Histone polysaccharide content is high, while Col II-Fe 2+ The content of histone polysaccharide was low. 12 weeks after surgery, Col II-Fe 3+ The proteoglycan secretion in the group was obvious, and it was significantly higher than that in Col II-Fe 2+ group, but no proteoglycan was formed in the Col II and blank groups. Saf-O / FG staining results showed that Col II-Fe 2+ and Col II-Fe 3+ The hydrogel significantly enhanced the secretion of proteoglycans. The ICRS histological scoring analysis results further confirmed the above observations. Figure 4 As shown in D.
[0050] The above description is only the details of individual exemplary implementation cases of the present invention. For those skilled in the art, the present invention may have various modifications and changes according to specific preparation conditions during actual application, and is not intended to limit the present invention. Anything within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. Application of iron ion cross-linked type II collagen gel in the preparation of drugs for the treatment of osteoarthritis.
2. The use according to claim 1, characterized in that The iron ion is Fe 3+ or Fe 2+ .
3. The use according to claim 2, characterized in that The iron ion is Fe 3+ .
4. The use according to claim 1, characterized in that The type II collagen is animal type II collagen.
5. The use according to claim 4, characterized in that: The type II collagen is yak type II collagen.
6. The use according to any one of claims 1 to 5, characterized in that: The preparation method of the iron ion cross-linked type II collagen gel is as follows: 3+ or Fe 2+ The solutions are mixed and reacted to obtain type II collagen gel cross-linked by iron ions.
7. The use according to claim 6, characterized in that The pH of the type II collagen solution is 4.5-7.0.